CLEAN DEVELOPMENT MECHANISM (CDM) AND RENEWABLE ENERGY PROJECTS: POTENTIAL REVENUE WHILST PROMOTING SUSTAINABLE DEVELOPMENT - hodl, verania (Agency for the Assessment and Application of Technology)
This paper explores examples of on going small scale renewable energy CDM projects. The picture of expected revenue and community’s benefits resulted from those projects are described. Numbers of CERs requested and issued are selected shown. Bundling several small-scale CDM projects that not exceed a total of 15 MW is described. This paper emphasis the importance of community participatory and explorative approaches in identification of local potentials as well as in conducting feasibility assessments.